Towards the decarbonization of the power sector – a comparison of China, the EU and the US based on historical data - Michel Noussan; Manfred Hafner; Loyle Campbell; Xinqing Lu; Pier Paolo Raimondi; Erpu Zhu (Fondazione Eni Enrico Mattei (FEEM), 2021)
This work compares the different decarbonization strategies of the power sector in China, the European Union and the United States, by considering the historical evolution of electricity generation and the current situation. Such a comparison is gaining a broader significance when evaluated with an additional level of geographic detail, by comparing European countries, Chinese provinces, and US states. The differences among these geographies highlight the challenges and opportunities of pushing towards low-carbon technologies, by making clear that regional decarbonization will need to address very different local contexts. Moreover, multiple policy and planning levels are involved, and those mechanisms are different in the three blocs being compared. Our analysis shows that these three blocs, although moving towards similar decarbonization targets, are currently at different levels of carbon intensity. The zero-carbon pathway will need to be declined in different local goals, based on the availability of low-carbon resources and the electricity demand. Given the geographical differences between demand and supply, and the likely increase of electricity demand, an improvement of power transmission networks will be essential. This work is part of a series of papers on the geopolitics of the energy transition in China, the European Union and the United States of America.
Keywords: N70; O13; P48; Q42; 330; Electricity; Power; Decarbonization; Energy Transition; China; EU; US